2000
DOI: 10.1017/s0958067000020431
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate ingestion prior to exercise augments the exercise-induced activation of the pyruvate dehydrogenase complex in human skeletal muscle

Abstract: During the transition from rest to steady-state exercise, a significant part of the energy necessary to sustain force generation is derived from PCr hydrolysis and glycogenolysis. Classically, the extent of this anaerobic ATP production through substrate level phosphorylation at the onset of exercise has been attributed to a lag in blood flow and oxygen delivery to the contracting muscle (Margaria et al. 1963). More recently, however, it has been demonstrated that the activity of PDC and the availability of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Five-to 10-mg frozen muscle was used to determine the active form of PDC (PDCa) (25). The time delay between sampling and freezing of the sample in liquid nitrogen (on average 10 -12 sec) was unlikely to have resulted in significant changes in PDC activity because the values obtained in the present study were comparable to values previously reported by our laboratory in which samples were snap frozen 2-3 sec after removal from the limb (26,27). LCACs and acetylcarnitine were determined enzymatically using RIAs (28).…”
Section: Muscle Sampling and Analysissupporting
confidence: 80%
“…Five-to 10-mg frozen muscle was used to determine the active form of PDC (PDCa) (25). The time delay between sampling and freezing of the sample in liquid nitrogen (on average 10 -12 sec) was unlikely to have resulted in significant changes in PDC activity because the values obtained in the present study were comparable to values previously reported by our laboratory in which samples were snap frozen 2-3 sec after removal from the limb (26,27). LCACs and acetylcarnitine were determined enzymatically using RIAs (28).…”
Section: Muscle Sampling and Analysissupporting
confidence: 80%
“…It is known that MCT can circumvent the block in the β-oxidation of long-chain fatty acids in VLCADD and can provide an alternative energy substrate to long-chain triglycerides (LCT) (Shiraev and Barclay, 2012), in addition to decreasing the oxidation of CHO, and reducing the risk of lactic acidosis induced by exercise (Behrend et al, 2012). Moreover, supplementation with CHO increases blood glucose levels and improves performance (Tsintzas et al, 2000). Accordingly, the role of this supplement was to (i) increase the work capacity during the test, (ii) maintain the glycemia level to reduce fat oxidation during recovery, and (iii) provide MCT for oxidation during the hours after assessment, thereby reducing the risk of post-exercise rhabdomyolysis (Diekman et al, 2016).…”
Section: Case Reportmentioning
confidence: 99%
“…Pre-exercise elevation of blood glucose and insulin increases glucose uptake and oxidation in 66 contracting skeletal muscle (Febbraio et al, 2000a,b;Tsintzas et al, 2000) through activation of 67 the pyruvate dehydrogenase enzyme complex (PDC). It has also been shown that 68 pharmacological activation of PDC reduces phosphocreatine degradation and muscle lactate 69 accumulation during short intense muscle contraction protocols (Timmons et al, 1998 …”
mentioning
confidence: 99%